Assessment of flickering chromatic pupillometry in patients with risk of glaucoma - Tripolone, María Constanza (2022)
Chromatic pupillometry is increasingly used for assessing human retinal function through measurements of pupil responses to different colored light stimuli. The discovery of intrinsically photosensitive retinal ganglion cells (ipRGCs) adds a new dimension to the detection and monitoring of retinal and optic nerve disorders, including open-angle glaucoma (OAG) through pupillometry. However, the detection of pre-perimetric glaucomatous deficits still remains a challenge. We hypothesize that early damage in OAG risk could be reflected in affected flickering pupil responses.